Re-Naming the Waters: ‘Southeast Asia Sea’ or ‘South Sea’? - Ellen, Frost (2016)
As Secretary of State John Kerry visits East Asia in search of a solution to the South China Sea imbroglio, analysts debate whether new ways out should be explored. One proposal is to change the name of the contested body of waters.